Comparison of Multilocus Sequence Typing and the Xpert C. difficile/Epi Assay for Identification of Clostridium difficile 027/NAP1/BI - McMillen, Tracy (J Clin Microbiol, 2016)
Clostridium difficile 027/NAP1/BI is the most common C. difficile strain in the United States. The Xpert C. difficile/Epi assay allows rapid, presumptive identification of C. difficile NAP1. We compared Xpert C. difficile/Epi to multilocus sequence typing for identification of C. difficile NAP1 and found “very good” agreement at 97.9% (κ = 0.86; 95% confidence interval, 0.80 to 0.91).